1991
DOI: 10.1002/bjs.1800780317
|View full text |Cite
|
Sign up to set email alerts
|

Primary repair of colon injuries in a developing country

Abstract: Because there are several specific disadvantages to a colostomy in a developing country, primary repair for colon injury was electively performed. Sixty-one consecutive patients with colon injury were seen between 1978 and 1989 and 57 of these (93 per cent) underwent primary repair. In four a colostomy was constructed. Emergency repair was carried out regardless of site or mode of injury, presence of hypotension or peritoneal contamination. There was one death unrelated to anastomotic complications and one ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In primary repair of wound, researchers used several options of primary repair with or without colostomy to check the effectiveness of repair without diversion [6][7][8][9][10][11][12][13][14] . Similar types of intervention had been adopted in developing countries too [15][16] . Researchers from Bangladesh are also assessing the outcome of primary repair of abdominal injuries in their clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…In primary repair of wound, researchers used several options of primary repair with or without colostomy to check the effectiveness of repair without diversion [6][7][8][9][10][11][12][13][14] . Similar types of intervention had been adopted in developing countries too [15][16] . Researchers from Bangladesh are also assessing the outcome of primary repair of abdominal injuries in their clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…On other hand, its higher than (16.25%)and(18.0%) reported by Adil KH et al (22) and G Jinescuetal (24) .In current study Wound infection was the commonest cause of post-operative complications (9.5%),followed by wound dehiscence (4.8%),while (3.6%) for both intestinal obstruction ,and pulmonary atelectasis as well as (2.4%) for both intra-abdominal abscess and pulmonary emboli .Adil K H et al (22) , found that wound infection was the main cause of post-operative complications detected in (7.5%)of cases followed by paralytic ileus and respiratory complications in (5%) of cases. Other studies conducted by Naraynsingh V et al (25), and Tahir I et al (11) , reported Higher percentage of wound infection which were (10%), and (58%) respectively. The rate of wound infection in the current study was within acceptable level.…”
Section: Discussionmentioning
confidence: 82%
“…Perforations with a localized paracolic abscess were excluded from analysis. Our unit has adopted a policy minimizing colostomy use as we have previously reported in a paper on colonic trauma and obstruction [13,14], since in Trinidad, there is limited public stoma acceptance and limited availability of stoma appliances. Patients were identified using the International Classification of Disease 9th Revision Clinical Modification (ICD-9 CM) admissions and discharge code 562.11.…”
Section: Methodsmentioning
confidence: 97%